2016 18th International Conference on Transparent Optical Networks (ICTON) 2016
DOI: 10.1109/icton.2016.7550618
|View full text |Cite
|
Sign up to set email alerts
|

Characterising refractive index dispersion in chalcogenide glasses

Abstract: Much effort has been devoted to the study of glasses that contain the chalcogen elements (sulfur, selenium and tellurium) for photonics' applications out to MIR wavelengths. In this paper we describe some techniques for determining the refractive index dispersion characteristics of these glasses. Knowledge of material dispersion is critical in delivering step-index fibres including with high numerical aperture for mid-infrared supercontinuum generation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…The refractive indices of Ge 16 As 24 Se 15.5 Te 44.5 and As 40 Se 60 from the present thin film measurements, a prism minimum deviation measurement (Fang et al 2016) and ellipsometry are shown in Fig. 7.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The refractive indices of Ge 16 As 24 Se 15.5 Te 44.5 and As 40 Se 60 from the present thin film measurements, a prism minimum deviation measurement (Fang et al 2016) and ellipsometry are shown in Fig. 7.…”
Section: Resultsmentioning
confidence: 99%
“…A hot-pressing technique was developed to prepare thin films of chalcogenide glass; this involved the hot-pressing of circa 20 mm lengths of fibre, with a nominal diameter of 250 lm, using the hot-press previously described in Fang et al (2016) (ICTON): Seddon et al (2006), Abdel-Moneim et al (2015). The as-annealed preforms (*10 mm diameter and *70 mm length) of Ge 16 As 24 Se 15.5 Te 44.5 and As 40 Se 60 , prepared as in Sect.…”
Section: Thin Film Sample Preparationmentioning
confidence: 99%
See 1 more Smart Citation